The Effect of Transport Time Interval on Neurological Recovery after Out-of-Hospital Cardiac Arrest in Patients without a Prehospital Return of Spontaneous Circulation - Park, Jeong Ho; Kim, Yu Jin; Ro, Young Sun; Kim, Sola; Cha, Won Chul; Shin, Sang Do (Journal of Korean medical science, 2019)
Longer transport adversely affects outcomes in out-of-hospital cardiac arrest (OHCA) patients who do not return to spontaneous circulation (ROSC). The aim of this study was to determine the association between the transport time interval (TTI) and neurological outcomes in OHCA patients without ROSC. We analyzed adult OHCA patients with presumed cardiac etiology and without prehospital ROSC from 2012 to 2015. The study population was divided into 2 groups according to STI (short STI [1-5 minutes] and long STI [≥ 6 minutes]). The primary exposure was TTI, which was categorized as short (1-5 minutes), intermediate (6-10 minutes), or long (≥ 11 minutes). The primary outcome was a good neurological recovery at discharge. Multiple logistic regression analysis was used in each STI group. Among 57,822 patients, 23,043 (40%), 20,985 (36%), and 13,794 (24%) were classified as short, intermediate, and long TTI group. A good neurological recovery occurred in 1.0%, 0.6%, and 0.3% of the patients in the short, intermediate and long TTI group, respectively. Among 12,652 patients with short STI, a good neurological recovery occurred in 2.2%, 1.0%, and 0.4% of the patients in the short, intermediate and long TTI group, respectively. Among 45,570 patients with long STI, a good neurological recovery occurred in 0.7%, 0.5%, and 0.3% of the patients in the short, intermediate and long TTI group, respectively. When short TTI was used as a reference, the adjusted odds ratios (AOR) of TTI for good neurological recovery was different between short STI group and long STI group (AOR [95% confidence interval, 0.46 [0.32-0.67] vs. 0.72 [0.59-0.89], respectively, for intermediate TTI and 0.31 [0.17-0.55] vs. 0.49 [0.37-0.65], respectively, for long TTI). A longer TTI adversely affected the likelihood of a good neurological recovery in OHCA patients without prehospital ROSC. This negative effect was more prominent in short STI group.